PENGARUH E-SERVICE QUALITY DAN E-TRUST TERHADAP E-SATISFACTION (Survei pada Mahasiswa Pengguna OVO di FISIP Universitas Lampung) - Fitriana, Indah (Jurnal Kompetitif Bisnis, 2021)
This study was aimed to find out the effect of e-service quality and e-trust in e-satisfaction of OVO users students in FISIP University of Lampung. This type of explanatory research with a quantitative approach. The data was obtained from a questionnaire, literature study and observation. The sampling technique used purposive sampling with a total sample of 363 people. Data analysis in this study used multiple linear regression analysis with SPSS 25.0 computer software. Based on the results of research and data analysis shows that e-service quality and e-trust simultaneously significantly affected e-satisfaction. While the partial test results of each variable showed that e-service quality and e-trust significantly affected e-satisfaction.